2019
DOI: 10.1101/586867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MeCP2 nuclear dynamics in live neurons results from low and high affinity chromatin interactions

Abstract: Loss of function mutations in Methyl-CpGbinding Protein 2 (MeCP2) cause the severe neurological disorder Rett Syndrome. MeCP2 is a highly abundant nuclear protein particularly enriched in neurons. Although biochemical and genomic analyses of MeCP2-DNA interaction and genomic distribution demonstrate that MeCP2 binding on chromatin is dependent on DNA modification state, the dynamic behavior of individual MeCP2 proteins in live neurons has not been explored. Here we use live-cell singlemolecule imaging to asses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…At the DNA level, our classifier model discovered that the direction of transcription rate shifts in human and mouse RTT models are best predicted by combinations of three dinucleotides that include the canonical MECP2-binding sites CA and CG, together with other dinucleotides including AT. The MECP2 AT-hook domain contributes to low-affinity transient interactions with AT-rich DNA that influence the dynamics of MECP2 binding to local high affinity methylated DNA sites 30 . Tellingly, the classifier predictions are low when modelling only CA/CG dinucleotide frequencies without accounting for low-affinity sites, and the accurate predictions are unaffected when low-affinity sites are included but the CA/CG dinucleotide frequencies are omitted.…”
Section: Discussionmentioning
confidence: 99%
“…At the DNA level, our classifier model discovered that the direction of transcription rate shifts in human and mouse RTT models are best predicted by combinations of three dinucleotides that include the canonical MECP2-binding sites CA and CG, together with other dinucleotides including AT. The MECP2 AT-hook domain contributes to low-affinity transient interactions with AT-rich DNA that influence the dynamics of MECP2 binding to local high affinity methylated DNA sites 30 . Tellingly, the classifier predictions are low when modelling only CA/CG dinucleotide frequencies without accounting for low-affinity sites, and the accurate predictions are unaffected when low-affinity sites are included but the CA/CG dinucleotide frequencies are omitted.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that in neurons the fraction of MeCP2 that is stably bound to chromatin is higher in comparison with the distribution of other transcription factors [ 113 ]. MeCP2 behavior in this context depends on both the integrity of its MBD and the DNA methylation [ 113 ].…”
Section: Readers Of Epigenetic Modifications That Control Pericentmentioning
confidence: 99%
“…It was recently demonstrated that in neurons the fraction of MeCP2 that is stably bound to chromatin is higher in comparison with the distribution of other transcription factors [ 113 ]. MeCP2 behavior in this context depends on both the integrity of its MBD and the DNA methylation [ 113 ]. Indeed, several mutations in the MBD of MeCP2 that can cause Rett syndrome, such as R106W, result in reduced binding of MeCP2 to methylated DNA [ 112 , 114 ], and an increased rate of MeCP2 diffusion in the nucleus [ 113 ].…”
Section: Readers Of Epigenetic Modifications That Control Pericentmentioning
confidence: 99%
See 1 more Smart Citation
“…SMT has been particularly successful in the nucleus to identify dynamic properties of chromatin-associated molecules such as transcription factors [2,3]. So far, several parameters of TF nuclear kinetics have been determined, including exact DNA binding times (ranging from a few seconds to 1–2 min), the TF fraction bound to DNA and localizations of transcriptional ‘hot-spots’ [411]. Previous studies have analysed the impact of cell stimulation by, for example, growth factor, hormone administration or DNA damage on TF-DNA interaction, and demonstrated that DNA occupancy and bound fraction of TFs such as p53, SRF, GR, ER, CREB and SOX2 are enhanced by cell activation [410].…”
Section: Introductionmentioning
confidence: 99%